Legal Position on Waqf Land That Is Not Registered as Bank Credit Guarantee: Case Study of Decision No. 0534/Pdt.G/2018/PA. Lmg - Rukmana, Dian; Judge, Zulfikar (Ann Publisher, 2023)
The purpose of preparing this thesis writing The author will also discuss the legal position of waqf land that is used as credit collateral in banks? And what are the legal consequences for land with waqf land rights that are used as credit collateral? Both expected and unexpected aspects of individuals, legal entities, organizations, institutions and social systems of society. This research is a normative juridical research with a qualitative approach so that the data collection technique used in this thesis is a literature technique, while the analysis in this study is after all legal materials are collected both from primary legal materials and secondary legal materials then clarified. qualitative according to the problem Based on literature search, this research has never been used before, thus this research is original and academically accountable. Although there are previous researchers who have conducted research on issues surrounding waqf, the substance of the subject matter discussed is different from this study. This research has a formulation of problems regarding legal consequences on land on the basis of waqf land rights that are used as credit guarantees.